2002
DOI: 10.1172/jci0214505
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid-activated nuclear receptor FXR suppresses apolipoprotein A-I transcription via a negative FXR response element

Abstract: Serum levels of HDL are inversely correlated with the risk of coronary heart disease. The anti-atherogenic effect of HDL is partially mediated by its major protein constituent apoA-I. In this study, we identify bile acids that are activators of the nuclear receptor farnesoid X receptor (FXR) as negative regulators of human apoA-I expression. Intrahepatocellular accumulation of bile acids, as seen in patients with progressive familial intrahepatic cholestasis and biliary atresia, was associated with diminished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
167
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(180 citation statements)
references
References 64 publications
8
167
1
1
Order By: Relevance
“…Yet, despite a considerable rescue of TICE activity in these mice there was very little effect on plasma cholesterol. It is therefore most conceivable that reduction of plasma cholesterol upon PX treatment in mice that do express hepatic FXR is due to suppressed transcription of apolipoprotein A-I 36 and enhanced expression of scavenger receptor class B-I (SCARB1/SR-BI) upon FXR activation, as reported previously by others. 37 In keeping with this hypothesis, we found upregulation of hepatic SR-BI mRNA as well as protein (data not shown).…”
Section: Discussionsupporting
confidence: 54%
“…Yet, despite a considerable rescue of TICE activity in these mice there was very little effect on plasma cholesterol. It is therefore most conceivable that reduction of plasma cholesterol upon PX treatment in mice that do express hepatic FXR is due to suppressed transcription of apolipoprotein A-I 36 and enhanced expression of scavenger receptor class B-I (SCARB1/SR-BI) upon FXR activation, as reported previously by others. 37 In keeping with this hypothesis, we found upregulation of hepatic SR-BI mRNA as well as protein (data not shown).…”
Section: Discussionsupporting
confidence: 54%
“…It has been found that dietary cholic acid decreases plasma HDL via downregulation of APO-AI levels [34][35][36] and greatly enhances intestinal cholesterol absorption, mainly by increasing intraluminal micellar cholesterol solubilization. 37 Our current results show that under the high cholesterol plus cholic acid feeding conditions, biliary cholesterol secretion is significantly increased in wildtype and Apob 48/48 mice, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand-activated FXR binds to response elements of target genes either as a classical FXRRXRa (retinoid X receptor alpha) heterodimer or as a monomer (2)(3)(4). FXR plays an important role in regulating the metabolisms of bile acid, cholesterol, triglyceride, and glucose (5).…”
Section: Introductionmentioning
confidence: 99%